10(r+10)=6(-7-2)-4r

Simple and best practice solution for 10(r+10)=6(-7-2)-4r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(r+10)=6(-7-2)-4r equation:


Simplifying
10(r + 10) = 6(-7 + -2) + -4r

Reorder the terms:
10(10 + r) = 6(-7 + -2) + -4r
(10 * 10 + r * 10) = 6(-7 + -2) + -4r
(100 + 10r) = 6(-7 + -2) + -4r

Combine like terms: -7 + -2 = -9
100 + 10r = 6(-9) + -4r

Multiply 6 * -9
100 + 10r = -54 + -4r

Solving
100 + 10r = -54 + -4r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '4r' to each side of the equation.
100 + 10r + 4r = -54 + -4r + 4r

Combine like terms: 10r + 4r = 14r
100 + 14r = -54 + -4r + 4r

Combine like terms: -4r + 4r = 0
100 + 14r = -54 + 0
100 + 14r = -54

Add '-100' to each side of the equation.
100 + -100 + 14r = -54 + -100

Combine like terms: 100 + -100 = 0
0 + 14r = -54 + -100
14r = -54 + -100

Combine like terms: -54 + -100 = -154
14r = -154

Divide each side by '14'.
r = -11

Simplifying
r = -11

See similar equations:

| tan58=6/x | | 9+2(2x+1)=1 | | 5+2k=3 | | 12/3=n | | x^6-2x=0 | | 9u^-4/9u^8 | | 27(p/3)*5(3p).6(2p).4(p) | | 10(r-2)=-5r | | 2u-16=4u-2 | | ln(5x+1)=4 | | z^2+9z=-25 | | 15E+6E=84 | | n/36=1/4 | | 2y=3(4-y) | | -x^2+12x=-19 | | 0.375z+2.25=0.8z-2.4 | | (4x-5)(x-7)=0 | | Sqrt(-x)=-1 | | 5/12=n/6- | | 3/27=9/n | | Ex+x=E | | (3x-5)=ln*306 | | 3x-5=5x+35 | | n/5=24/10 | | 2x+50=2+6x | | G(x)=1.1-ln(2x+5) | | -2x=-x^2-5x+12 | | -7+-18y+18=30y+20+3 | | 5x+y=163 | | 9/n=1/9 | | 6w+0.19=55.39 | | 2x^2-3x=11 |

Equations solver categories